PENGARUH APLIKASI WORDWALL TERHADAP KEMAMPUAN BERHITUNG PERMULAAN ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA NANGA TAMAN - Humaira, Aprila; R, Marmawi; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to describe the effect of the wordwall application on early numeracy skills of children aged 5-6 years at TK Pembina Negeri Nanga Taman. The method used was a quantitative experimental method, the research subjects were class B with 11 children. The results of the study showed that the effect of the wordwall application on early numeracy skills of children aged 5-6 years in this study was very good, early numeracy abilities at pretest were 73% in the MB category, 27% in the BSH category, while at posttest 64% were in the BSH category, 36 % BSB category. with a difference of 27.84%, indicating a change in the achievement of early numeracy skills in children aged 5-6 years at TK Pembina Nanga Taman. The results of the research show that if you compare the rcount with the r-table where N=11 at the 5% significance level, we get -ttable tcount ttable with the result -3.82201 -2.80659 3.82201. Thus it can be concluded that there is The influence of the wordwall application on early numeracy skills of children aged 5-6 years at TK Pembina Negeri Nanga Taman.